Cloning of a Beta-Hemolysin Gene of Brachyspira (Serpulina) hyodysenteriae and Its Expression in Escherichia coli - Hsu, Tsungda (American Society for Microbiology, 2001)
Brachyspira (Serpulina) hyodysenteriae induces a mucohemorrhagic diarrheal disease in pigs. The production of a beta-hemolysin has been considered a major virulence attribute of this organism. Previous reports have failed to correlate a specific cloned gene sequence with a purified beta-hemolytic protein sequence. Thus, questions still remain concerning the structural gene sequence of the hemolysin. To answer this question unequivocally, the beta-hemolytic toxin was purified from extracts of log-phase spirochetes, and the N-terminal amino acid sequence was determined (K-D-V-V-A-N-Q-L-N-I-S-D-K) and compared with the translated sequences of previously cloned genes, tlyA to tlyC. The lack of homology between tlyA to tlyC translated sequences and the purified beta-hemolytic toxin sequence resulted in the study that is reported here. A degenerate probe was designed based on the N-terminal amino acid sequence of the purified beta-hemolysin and used to screen a B. hyodysenteriae genomic library. Three overlapping clones were identified, and one was sequenced to reveal an open reading frame coding for a putative 8.93-kDa polypeptide containing the N-terminal sequence of the purified beta-hemolysin. To distinguish this gene from the tlyA to tlyC genes, it has been designated hlyA. A hemolysis-negative Escherichia coli strains containing hlyA was beta-hemolytic on blood agar media. Also, the hemolytic activity of the recombinant protein had identical protease and lipase sensitivities and electrophoretic mobility to those of native B. hyodysenteriae beta-hemolysin. Based on sequence analysis, the translated protein had a pI of 4.3, an α-helical structure, and a phosphopantetheine binding motif. Hybridization analysis of genomic DNA indicated that the hlyA gene was present in B. hyodysenteriae and B. intermedia but was not detected in B. innocens, B. pilosicoli, or B. murdochii under high-stringency conditions. The location of hlyA on the chromosomal map was distinct from the locations of tlyA, tlyB, and tlyC.